Seasonal incidence of white stem borer, Scirpophaga fusciflua Hampson on paddy in Himachal Pradesh - Tandon, Vikas; Srivastava, Ajai (ORYZA-An International Journal of Rice, 2018)
Field experiments were conducted to study the seasonal incidence of white stem borer on paddy during Kharif season 2015-2017. The data revealed that larval population and per cent plant infestation were noted from 30 th standard meteorological week (SMW) and remained up to 42th SMW. The peak larval population infestation was observed at 39th SMW. The maximum cumulative dead hearts (DH) and white ears (WE) were observed at 35th and 39th SMW, respectively. Maximum temperature was found to be positively correlated with larval population as well as per cent plant infestation. However, rainfall and relative humidity were observed to be negatively correlated. To plan the different suitable control measures for the pest, knowledge of population dynamics is very much essential. It is also useful in development of forecasting model for pest.